Waktu Tempuh Perjalanan Penduduk Perumahan Puri Yuhana Permai dan Bukit Khatulstiwa - Gideon Irianto Minanga; Rais Rachman; Monika D.M Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
The phenomenon that occurs in Makassar City in terms of travel time is that there are more private vehicle users compared to users of public transportation services. The rapid economic growth in Makassar City affects the people's purchasing power and increases the number of motor vehicle ownership. As a consequence, the trips are longer and the travel time needed is longer and longer than using private vehicles. This study aims to identify the independent variables that affect the travel time of workers who live in Puri Yuhana Permai Housing and Khatulisiwa Hill to get to work, and model travel time based on independent variables that are significant to the travel time of these workers using the multiple linear regression method SPSS 22.0. . The results of the research on each housing show that the variables that have a significant effect on the travel time of Puri Yuhana Permai housing are the mode (X3) and the distance traveled (X4), and the Khtulisiwa Hill is the distance traveled (X4). And it is known that the dominance of the travel time sequence of the Yuhana Yuhana housing complex (15-30 minutes) 47.3%, (30-45 minutes) 32.7%, (<15 minutes) 10.9%, (60 minutes) 9,1 %. Meanwhile, for Bukit Khatulistiwa Housing (15-30 minutes) 37.3%, (30-45 minutes) 28%, (<15 minutes) 18.7%, (60 minutes) or 16%.